The Trends In Educational Management Research And Its Implications To Higher Education: A Bibliometric Analysis - Daryono (Ilomata International Journal of Social Science, 2023)
A research in management of a higher education field has a significant benefit in optimizing the quality of education. The aims of this research are to explain the trends in publication research on management of higher education and its implication to the next developmental researches. This research uses bibliometric analysis method with the data from the most frequently accessed index, Google Scholar database. The Data are collected from the available publications in Google scholar by searching the keywords on management, educational management, and management of higher education through the titles, the abstracts, as well as the keywords using the publish and perish software. The finding from the research mapping indicates that researchers tend to team up collectively in their institution. The majority of management researches in higher education is still dominated by researchers who adopt the function of educational management as the scientific sources in developing the management of higher education. The researchers recommend conducting a number of joint researches between institutions and cross countries to enrich scientific integration and propose some considerations to the policy makers for setting up a more efficient and comprehensive management policy of the higher education.